Correlation of ERG immunohistochemistry with molecular detection of TMPRSS2-ERG gene fusion. Issue 7 (15th December 2015) - Sung, Ji-Youn; Jeon, Hwang Gyun; Jeong, Byong Chang; Seo, Seong Il; Jeon, Seong Soo; Lee, Hyun Moo; Choi, Han Yong; Kang, So Young; Choi, Yoon-La; Kwon, Ghee Young
Abstract : Aims: TMPRSS2/ E26 transformation-specific (ETS) family gene fusion in prostate carcinoma (PCa) can be detected by several methods including immunohistochemistry (IHC) for ETS-related gene (ERG), the diagnostic utility of which has not been clearly defined. Methods: We explored TMPRSS2-ERG gene rearrangement status in 132 patients with PCa with four detection methods including fluorescence in situ hybridisation for TMPRSS2-ERG fusion, real-time reverse transcription PCR (RT-qPCR) for ERG and TMPRSS-ERG fusion transcript mRNA and IHC for ERG. Results: Concordant results were found in 126 cases for the four detection methods and the remaining six cases showed discrepancy in one method: two cases in IHC, three cases in RT-qPCR for ERG and one case in RT-qPCR for fusion transcript. In discordant cases, the majority results were determined as final fusion status. Analysis of discrepancy cases for ERG IHC showed that weak immunoreactivity for ERG should be regarded as equivocal and that even strong immunoreactivity can be false positive. The overall incidence of TMPRSS-ERG gene fusion was 24%. Conclusions: ERG IHC is a useful surrogate test for the detection of TMPRSS2-ERG gene fusion, but it needs to be interpreted with caution and definite judgement should not be based on IHC alone. A relatively low incidence of TMPRSS2-ERG gene fusion was demonstrated in this Korean cohort.